Analisis Faktor-Faktor Yang Mempengaruhi Fungsi Di Tempat Kerja Pada Perawat - Septiani Hestri Murti; Nang Among Budiadi; Sugiyarmasto Sugiyarmasto (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Background: The workplace function of nurses is an important thing that must be paid attention to by hospitals. Nurses certainly have an important function in their work in terms of health services. Employees should be able to adapt and be respected in their work environment. However, some people experience problems adapting to their work environment, resulting in low performance. Nurses' decreased function at work due to high workloads makes it difficult to control one's own behavior. This results in the implementation of the work not being optimal.Objective: This study was conducted to examine the factors that influence workplace function in nurses Method: This research is a quantitative research with a survey design. Research data was collected using a questionnaire from respondents who work as nurses in hospitals. The sampling technique used purpose sampling technique and the sample size was 200 nurses. This research uses SEM (Structural Equation Modeling) analysis using AMOS and regression analysis using SPSS. Results: Based on the results of the analysis that has been carried out, the research results show: self-regulation capacity has a significant effect on functioning at work, self-regulation capacity has a significant effect on self-destruction, self-regulation capacity has a significant effect on job craftsmanship, self-destruction has a significant effect on functioning at work. workplace, work craft has a significant influence on function in the workplace. Burnout does not moderate the relationship between self-regulatory capacity and functioning at work so it does not have a significant influence. Conclusion: Increased functioning in the workplace for nurses is influenced by optimal self regulation capacity in nurses, self-destruction which can be increasingly minimized, work craftsmanship which increases in nurses.